Evaluation of hospital length of stay and revenues as a function of admission mode, clinical pathways including observation unit stay and hospitalization characteristics. (February 2019) - Casalino, Enrique; Perozziello, Anne; Choquet, Christophe; Curac, Sonia; Leroy, Christophe; Hellmann, Romain
Objectives: Hospital length of stay (days) and revenues per day (euros) could be different depending on admission mode. To determine the impact of admission mode as a function of clinical pathway, we conducted the present study. Data sources : We included 159, 206 admissions to three academic hospitals during a four-year period. Data were obtained from the electronic system of the hospital trust. Study design: A case (through-emergency department)–control (elective (EA)) study was conducted (77, 052), matched by age, stay severity and type, disease-related group, and discharge mode. Principal findings : Through-emergency department were significantly elderly, more severe, had more intensive care stays, a higher mortality rate, longer length of stay (days) (9.5 ± 12 vs. 6.8 ± 9.5; p < 0.0001), and lower revenues per day (647 ± 451 vs. 721 ± 422; p = 0.01). In case–control study, mean differences between cases and controls were: longer length of stay −0.64 and revenues per day −75.6; for ≥75 years −1.2 and −102.1; medical −0.9 and −90.4; and discharge to facilities care centers −1.5 and −81.8. Among cases, 40% had a stay in observation unit before being admitted in hospital ward. Differences were strongly reduced for patients who did not go to observation unit before being admitted. Differences were reduced from 0.64 to 0.2 days for length of stay and from 79 to 41 euros for revenues per day when patients did not stay in observation unit before being admitted. Conclusions: We conclude that admission mode is associated with length of stay and revenues. However, as differences are weak, elective admissions should not be prioritized on economic arguments. Otherwise, our study indicates that among through-emergency department admissions, observation unit stay is associated with longer length of stay and lower revenues.